Notes on geminates in Sesotho - Riedel, Kristina; Lee, Seunghun J. (Stellenbosch Papers in Linguistics Plus, 2023)
Geminates are a feature of Sesotho phonology. Only nasals and the lateral appear as geminates, to the exclusion of the other sonorants that form part of the Sesotho phonemic inventory. This squib reports on some phonetic and phonological aspects of Sesotho geminates, including duration, the phonotactic distribution of geminates and the syllabic structures in which they appear.